IMPLEMENTASI PEMBELAJARAN BERBASIS LESSON STUDY UNTUK MENGEMBANGKAN KARAKTER KEMANDIRIAN BELAJAR SISWA KELAS VII C SMP NEGERI 9 JEMBER SEMESTER GENAP TAHUN AJARAN 2013/2014 PADA SUB POKOK BAHASAN GARIS DAN SUDUT - Chandrasari, Titis Rini; Trapsilasiwi, Dinawati; Kurniati, Dian (KadikmA, 2015)
Abstract. Lesson Study is an effort to improve the quality of learning and development of teacherâs professionality. The aim of implementation learning based Lesson Study in class VII C SMP Negeri 9 Jember to develop a character learning independence of students. Lesson Study based learning in this research went smoothly and accordance with the planned stages. The result shows the development of character learning independence from cycle I to cycle III. Lesson Study based learning is able to develop a character learning independence. It is show by a rise in the percentage of each indicator that shows the character learning independence. Key Words : Lesson Study, Learning Independence